Pre-Visit Planning Calls Conducted by Student Pharmacists at a Student-Run Free Clinic - Maranets, Michael; Harmer, Kathryn; Vordenberg, Sarah; Thompson, Amy (Journal of Student-Run Clinics, 2022)
Background: Student pharmacist participation in Student-Run Free Clinics (SRFCs) has not been well studied. Similarly, there is not much data for the use of pre-visit planning calls in the SRFC setting. Our SRFC is open two days a week and staffed by a multidisciplinary team of medical, nursing, pharmacy, and social work students that are supervised by physicians, nurse practitioners, pharmacists, and clinical social worker preceptors. The objective of our project is to determine the impact of pre-visit telephone calls on the accuracy of existing medication lists in the electronic health record (EHR) and the identification of medication therapy-related problems. Methods: We developed a pre-visit planning call protocol to perform medication reconciliation and identify medication therapy problems (MTPs). Trained student pharmacists called patients prior to their scheduled medical appointment to update their medication list in the EHR and conduct a preliminary assessment of MTPs. We recorded patient demographics, including age, gender, race, co-morbid conditions, medication changes documented in the EHR, and potential MTPs. Descriptive statistics were used to describe the patient population and medication changes. Results: A total of 111 patients participated in 135 patient encounters. Among prescription medications, there were 36 additions, 34 removals, and 97 adjustments to directions. There were 147 nonprescription products added, 34 removed, and 56 adjustments to directions. There were 16 situations in which a patient may have needed additional medication therapy, 14 drug-drug interactions, 12 adverse medication events, and five problems requiring additional monitoring. The median call was 5 minutes in duration. Conclusion: Student pharmacists were able to conduct pre-visit planning telephone calls to improve the accuracy of medication lists and conduct a preliminary assessment of MTPs prior to patient visits at the SRFC.